Information Security and Knowledge Management - Ike, Ellena (European Journal of Information and Knowledge Management, 2024)
Purpose: The general objective of the study was to analyze information security and knowledge management. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to information security and knowledge management. Preliminary empirical review revealed that integrating IS and KM was crucial for enhancing organizational performance, protecting intellectual assets, and fostering innovation. It emphasized the need for a holistic approach combining technological solutions, robust policies, and a culture of security awareness. The research found that this integration led to significant improvements in operational efficiency and innovation, with continuous evaluation and adaptation being essential. The study highlighted the importance of advanced security technologies, regular updates, and employee training to maintain effective IS and KM practices, ultimately ensuring the secure and effective utilization of knowledge assets for sustainable growth. Unique Contribution to Theory, Practice and Policy: The Socio-Technical Systems Theory, Knowledge-Based View of the Firm and Information Systems Success Model may be used to anchor future studies on information security and knowledge management. The study provided significant contributions to theory, practice, and policy by integrating various theoretical frameworks and emphasizing the need for a multi-layered approach to IS that includes advanced technology, strong policies, and employee training. It recommended the development of regulatory standards to enforce robust IS practices, the alignment of IS and KM with organizational strategies, and the implementation of continuous improvement programs. Additionally, it highlighted the importance of comprehensive training for employees and fostering a collaborative environment that balances security with innovation.